Researches Benchmarking for Identifying the Relationship between Innovation and Entrepreneurship in E-commerce - Alahverdi, Amir Ali (International Review of Management and Marketing, 2017)
The unique features of e-commerce and communications resulted in the development of business and employment to cause the promotion of entrepreneurship in the aspect of training the personality traits of entrepreneurship and entrepreneurial idea making. In addition, there is a mutual interactive relationship between entrepreneurship and e-commerce. In this base, governments must develop and reinforce the platform of entrepreneurship in the area of e-commerce which is the same as communication and information networks. The purpose of this research is to analyze researches’ benchmarking for identifying the relationship between innovation and entrepreneurship in e-commerce. In purpose aspect, this study is practical and in data collection aspect is descriptive and survey. Results indicated that the improvement of customer relationship in e-commerce and business causes sustainable competitive advantage and it reduces the costs of organizations. Unemployment can also be reduced with a low capital. Moreover, introducing a practical framework to help organizations achieve their purposes causes entrepreneurship to thrive, and organizations to gain a correct and timely perception of market situation. Keywords: E-commerce, entrepreneurship, innovation, benchmarking, information technology JEL Classifications: L26, L81, O3